2010
DOI: 10.1002/ajmg.a.33362
|View full text |Cite
|
Sign up to set email alerts
|

Severe pulmonary emphysema in a girl with interstitial deletion of 2q24.2q24.3 including ITGB6

Abstract: Owing to the large size of chromosome 2, partial monosomy of the long arm of this chromosome gives rise to many specific phenotypes. We report on a 2-month-old girl with an interstitial deletion of 2q24.2q24.3, which was confirmed by microarray-based comparative genomic hybridization analysis. The patient showed delayed growth and mental retardation, early myoclonic seizures, and characteristic dysmorphic features including thick arched eyebrows, upslanting palpebral fissures, long eyelashes, depressed nasal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…They described a patient with ID and growth retardation associated with a tiny deletion in the chromosomal region 2q24.2 containing only TBR1 . In contrast to the earlier published cases with larger deletion sizes (Krepischi et al, ; Magri et al, ; Palumbo et al, ; Takatsuki et al, ; Traylor et al, ) this patient shows a minor phenotypical manifestation as the deletion affects only one gene. Patient 331488 from DECIPHER has a 0.462 Mb deletion and shows a global development delay.…”
Section: Discussioncontrasting
confidence: 91%
“…They described a patient with ID and growth retardation associated with a tiny deletion in the chromosomal region 2q24.2 containing only TBR1 . In contrast to the earlier published cases with larger deletion sizes (Krepischi et al, ; Magri et al, ; Palumbo et al, ; Takatsuki et al, ; Traylor et al, ) this patient shows a minor phenotypical manifestation as the deletion affects only one gene. Patient 331488 from DECIPHER has a 0.462 Mb deletion and shows a global development delay.…”
Section: Discussioncontrasting
confidence: 91%
“…Deletions of various sizes spanning the 2q21q31 region have been reported in over 100 cases and are associated with a broad spectrum of phenotypic features [Pereira et al, 2004;Langer et al, 2006;Pescucci et al, 2007;Davidsson et al, 2008;Newbury et al, 2009;Chen et al, 2010;Krepischi et al, 2010;Takatsuki et al, 2010;Magri et al, 2011;Palumbo et al, 2012], including seizure disorder [Grosso et al, 2008]. Substantial evidence indicates that the sodium channel (SCN) ␣ subunit genes of the 2q24.3 region, in particular SCN1A , induce the seizure phenotype when mutated or deleted [Davidsson et al, 2008;Escayg and Goldin, 2010], although there is evidence for the contribution of SLC4A10 at 2q24.2 to a milder seizure phenotype when deleted [Krepischi et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the chromosomal aberration, we performed aCGH analysis using Human Genome CGH Microarray 44A (Agilent Technologies, Palo Alto, CA, U.S.A.) with genomic DNA extracted from the patient’s peripheral blood according to the method described elsewhere (Takatsuki et al., 2010). Metaphase or prometaphase chromosomes were prepared from phytohemagglutinin‐stimulated peripheral blood lymphocytes for two‐color fluorescence in situ hybridization (FISH) analysis using bacterial artificial chromosome (BAC) clones as probes as described previously (Takatsuki et al., 2010). BAC clones were selected from an in silico library (UCSC Human Genome Browser, March 2006 http://genome.ucsc.edu/).…”
Section: Methodsmentioning
confidence: 99%
“…Chromosomal deletions of 2q21‐q31 have been known to be closely related to seizures and epilepsies, and the band 2q24 is the smallest commonly deleted segment in these patients (Davidsson et al., 2008). Several authors including us have reported that deletions of the voltage‐gated sodium channel (SCN) cluster at 2q24 are associated with several epilepsy syndromes (Takatsuki et al., 2010). The deletions of the locus, including SCN1A, were found in patients with Dravet syndrome (Marini et al., 2009; Suls et al., 2010).…”
mentioning
confidence: 99%